Synthesis of CaO·2MgO·8Al2O3 (CM2A8) and its slag resistance mechanism. Issue 4 (April 2017) - Chen, Junhong; Chen, Haiyang; Mi, Wenjun; Cao, Zheng; Li, Bin; Li, Guangqi
Abstract: CM2 A8 is a solid solution of MA and CA6 . As a component in the ternary phase diagram of CaO-Al2 O3 -MgO, it was not reported in detail. So in this work, analytically pure CaO, MgO and Al2 O3 were adopted as starting materials and batched stoimotrically according to CM2 A8 . The raw materials were ground, mixed, shaped and reaction-sintered at different temperatures (1550 °C, 1650 °C, 1700 °C, and 1750 °C) to synthesize CM2 A8 . The synthesized specimens were analyzed by XRD, SEM, and TEM and the corrosion mechanism against LF slag was also researched. The results show that high-purity CM2 A8 can be synthesized by reaction sintering at 1750 °C. During synthesis, granular MA and flake CA6 form and grow together; at 1650 °C, they solid-solve together to form C2 M2 A14 . As the temperature rises, solid solution reaction goes on, which results in the disappearance of CA6, C2 M2 A14, and MA in succession and forms high-purity CM2 A8 growing towards hexagonal column crystals. In the high temperature reaction between CM2 A8 and steel slag, Ca 2+ in the slag reacts with CM2 A8 to form CA2, damaging the structure of CM2 A8 and releasing excessive Mg 2+ and Al 3+ which move towards the molten slag. As the reaction between Ca 2+ and CM2 A8 proceeds, a dense CA2 coating forms on the surface of CM2 A8 . The slag viscosity increases as well because of the entrance of Mg 2+ and Al 3+ . Thus, the formation of the CA2 coating and the enhancement of the slag viscosity restrain the penetration and corrosion of slag towards CM2 A8 .